(untitled) (Kerala Journal of Psychiatry, 2019)
Background: Suicide is one of the top ten leading causes of death in the world as well as India. Poisoning is one of the most common modes of attempting suicide. Self-immolation is a devastating form of suicide attempt. Impulsivity has been demonstrated as an important risk factor for suicide. Lethality and intent were found to be interrelated in previous studies. But a comparative study of impulsivity, lethality and intent between self-immolation and poisoning was not found in a literature search. Objectives: • To compare socio-demographic characteristics, impulsivity, intent and lethality in those who attempt suicide by self-immolation and poisoning. • To find the intercorrelations between intent, impulsivity and lethality. Methods: A cross-sectional comparative study was done among persons attempting suicide by self-immolation (n=40) and poisoning (n=50). Barratt’s impulsivity scale, Smith’s LSARS (lethality of suicide attempt rating scale) and Beck’s suicide intent scale were used to assess impulsivity, lethality and intent, respectively. Percentages, mean, median and range were used to describe the data. Chi-square test, t-test and Pearson correlation were used for statistical analysis. Results and discussion: There were significant associations between occupation, family income and socioeconomic status and mode of suicide attempt. Lethality was higher in self-immolation. Lethality and intent were significantly intercorrelated in both groups. Impulsivity and lethality were negatively correlated in the self-immolation group. Conclusion: Self-immolation is a highly lethal method of attempting suicide. Highly lethal suicide attempts have high intent. Greater the impulsivity, less lethal the attempt is likely to be.